Interactive histone acetylation and methylation in regulating transdifferentiation‐related genes during tunicate budding and regeneration. Issue 1 (24th October 2014) - Shibuya, Misa; Hatano, Mitzuki; Kawamura, Kaz
ABSTRACT Background: In the budding tunicate Polyandrocarpa misakiensis, retinoic acid (RA)‐triggered transdifferentiation occurs during bud development and zooid regeneration. We aimed to reveal how and to what extent epigenetic histone modifications are involved in transdifferentiation‐related gene expression. Results: Acetylated histone H3 lysine 9 (H3K9ac) was observed in transdifferentiating bud tissues and regenerating zooid tissues, where a histone acetyltransferase (HAT) gene, PmGCN5, was strongly expressed. Results of chromatin immunoprecipitation (ChIP) indicated that in transdifferentiating bud tissues, retinoic acid receptor (PmRAR), retinoid X receptor (PmRXR), external signal‐regulated kinase (PmERK), and β‐catenin (PmβCTN) genes conspicuously underwent H3K9 acetylation in their core promoter regions. RA was found to induce PmGCN5, causing histone acetylation of PmRAR, PmRXR, and PmERK. A GCN5 inhibitor, CPTH2, attenuated acetylation and weakened transcription of transdifferentiation‐related genes, except PmERK, indicating that RA‐induced GCN5 facilitates gene expression via histone acetylation. In regenerating zooids, H3K9ac occurred exclusively in PmERK, but PmERK expression did not change, and, surprisingly, the PmProhibitin2 expression decreased substantially. In the core promoter regions of these genes, suppressive histone methylation occurred at H3K9 and H3K27. Conclusions: These results, along with other evidence, indicate that cooperative and conflicting histone modifications enable the minute regulation of gene expression in P. misakiensis. Developmental Dynamics 244:10–20, 2015. © 2014 Wiley Periodicals, Inc.